2012
DOI: 10.1007/s10006-012-0381-2
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycotic osteomyelitis of the mandible: an unusual case

Abstract: In this case, the causative agent was Actinomyces, which makes it even more unusual. The origin of the microorganism has not been clearly established; however, the diagnosis allowed long-term treatment with antibiotics, which has resulted in the resolution of the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
(46 reference statements)
1
16
0
2
Order By: Relevance
“…Maxilla and temporomandibular joint are comparatively resistant for the disease and prevalence is a ratio mandible:maxilla of 4:1. It is assumed that mandible is more commonly affected than maxilla due to the lesser vascularity and the denser cortical bone, similar to osteoradionecrosis [10]. In this case, coinfection of cervicofacial and thoracic type was shown by invasion of symphysis and lung.…”
Section: Introductionmentioning
confidence: 71%
“…Maxilla and temporomandibular joint are comparatively resistant for the disease and prevalence is a ratio mandible:maxilla of 4:1. It is assumed that mandible is more commonly affected than maxilla due to the lesser vascularity and the denser cortical bone, similar to osteoradionecrosis [10]. In this case, coinfection of cervicofacial and thoracic type was shown by invasion of symphysis and lung.…”
Section: Introductionmentioning
confidence: 71%
“…CFA is the most common form of actinomycotic infection10. In addition to CFA, actinomycotic infection is a potential complication in bisphosphonate-related osteonecrosis of the jaw and osteoradionecrosis11.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of antibiotics, the implementation of incision and drainage of abscesses, and with the removal of infected teeth, most infections can usually be treated fast and successfully [ 1 , 2 , 3 , 4 , 5 ]. Nevertheless, sometimes persistent subacute and chronic infections occur, where adequate therapy can be a great challenge for practitioners and where treatment can take a long time [ 6 ]. Especially, delayed-onset wound infections after third molar extraction, which occur several weeks after suture removal and after discharge [ 7 ], can cause varying symptoms affecting hard and soft tissues [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figueiredo et al reported that those infections are normally caused by anaerobic bacteria of the oral flora, e.g., Fusobacterium, Peptostreptococcus , Porphyromonas, and Prevotella strains, which in most cases can be successfully treated with combinations of surgical revision and antibiotics [ 9 ]. Other authors have shown that specific infections like Actinomycosis, which need specific therapy, have to be considered [ 6 , 12 , 13 ]. Additionally, cases of osteomyelitis of the jaw after third molar surgery have been previously described [ 14 ].…”
Section: Introductionmentioning
confidence: 99%